Atelectasis Induced by Thoracotomy Causes Lung Injury during Mechanical Ventilation in Endotoxemic Rats - Choi, Won-Il (The Korean Academy of Medical Sciences, 2008)
Atelectasis can impair arterial oxygenation and decrease lung compliance. However, the effects of atelectasis on endotoxemic lungs during ventilation have not been well studied. We hypothesized that ventilation at low volumes below functional residual capacity (FRC) would accentuate lung injury in lipopolysaccharide (LPS)-pretreated rats. LPS-pretreated rats were ventilated with room air at 85 breaths/min for 2 hr at a tidal volume of 10 mL/kg with or without thoracotomy. Positive end-expiratory pressure (PEEP) was applied to restore FRC in the thoracotomy group. While LPS or thoracotomy alone did not cause significant injury, the combination of endotoxemia and thoracotomy caused significant hypoxemia and hypercapnia. The injury was observed along with a marked accumulation of inflammatory cells in the interstitium of the lungs, predominantly comprising neutrophils and mononuclear cells. Immunohistochemistry showed increased inducible nitric oxide synthase (iNOS) expression in mononuclear cells accumulated in the interstitium in the injury group. Pretreatment with PEEP or an iNOS inhibitor (1400 W) attenuated hypoxemia, hypercapnia, and the accumulation of inflammatory cells in the lung. In conclusion, the data suggest that atelectasis induced by thoracotomy causes lung injury during mechanical ventilation in endotoxemic rats through iNOS expression.